3D Ag@C Cloth for Stable Anode Free Sodium Metal Batteries. Issue 4 (18th January 2021) - Wang, Hui; Wu, Yan; Liu, Shihao; Jiang, Yang; Shen, Dong; Kang, Tianxing; Tong, Zhongqiu; Wu, Di; Li, Xinjian; Lee, Chun‐Sing
Abstract: While sodium metal anodes (SMAs) feature many performance advantages in sodium ion batteries (SIBs), severe safety concerns remain for using bulk sodium electrodes. Herein, a 3D Ag@C natrophilic substrate prepared by a facile thermal evaporation deposition method, which can be employed as a much safer "anode‐free" SMA, is reported. Initially, there is no bulk sodium on the Ag@C substrate in the assembled SIBs. Upon charging, sodium will be uniformly deposited onto the Ag@C substrate and afterwards functions as a real SMA, thus inheriting the intrinsic merits of SMA and enhancing safety simultaneously. While cycling, the as‐synthesized substrate demonstrates superior sodium plating/stripping cycling stability at 1, 2 and 3 mA cm −2 with a capacity of 2 mAh cm −2 . Theoretical simulations reveal that Na ions prefer to bind with Ag and form a Na‐Ag network, thus clearly revealing uniform sodium deposition on the Ag@C substrate. More importantly, a full battery based on Ag@C and Prussian white with impressive Coulomb efficiency (CE), high rate capability (from 0.1 C to 5 C) and long‐term cycling life is illustrated for the first time, thus making Ag@C feasible for the establishment of "anode‐free" SIBs with reduced cost, high gravimetric/volumetric energy density and enhanced safety. Abstract : A 3D Ag@C substrate, featuring facile electrons and sodium ions accessibility, enables stable Na ion deposition as uncovered by theoretical simulations and experimental analyses. Paired with a Prussian white cathode, this anode‐free sodium metal full cell yields high capacity, superior Coulomb efficiency and reasonable capacity retention of ≈56% over 800 cycles at 0.5 C rate.